Semisolid microstructure evolution of AZ91D magnesium alloy refined by Al-Ti-B - Chen,Ti Jun (2011)
The microstructural evolution and corresponding phase transformations have been investigated during partial remelting of AZ91D magnesium alloy refined by Al-Ti-B master alloy. The effect of heating temperature on semisolid microstructure has also been discussed. The results indicate that the microstructural evolution process includes four stages, the initial rapid coarsening, structure separation, spheroidization accompanied by coarsening and the final coarsening. Two or more equiaxed dendrites in the as-cast microstructure evolve into one spheroidal primary particle in the semisolid microstructure through the former three stages. The initial rapid coarsening results from the reaction of β→α, the structure separation is due to the α + β→L and α→L, the spheroidization is attributed to the α→L and the final coarsening is ascribed to the two reverse reactions of α→L and L→α. Rising the heating temperature during partial remelting is beneficial for obtaining small and spheroidal primary particles.